The biogeography and co-occurrence network patterns of bacteria and microeukaryotes in the estuarine and coastal waters. (February 2023) - Wu, Jinnan; Zhu, Zhu; Waniek, Joanna J.; Niu, Mingyang; Wang, Yuntao; Zhang, Zhaoru; Zhou, Meng; Zhang, Ruifeng
Abstract: Community and diversity shifts of bacteria and microeukaryotes with strong environmental and spatial variations have been unveiled in the Pearl River Estuary (PRE) and northern coastal part of South China Sea (SCS). However, it is not clear what the determining factors shape the microbial community and how the biotic interactions respond to the estuarine and oceanic environment. Here, we established the multiple regression models (MRM) and co-occurrence networks on microbial communities in PRE and SCS habitats. The results showed that there were significant differences of the abiotic factors affecting the bacterial and microeukaryotic communities between PRE and SCS habitats. Salinity explained the largest variations to the microbial community dissimilarities in PRE. Whereas spatial and environmental factors determined the microbial community dissimilarities in SCS. Positive relations between parasitic lineages (e.g. Perkinsea and Cercozoa) and algal taxa (Dinophyceae, Cryptophyta, Chlorophyta and Ochrophyta) dominated in the PRE network. While parasites Syndiniales positively correlated with other Syndiniales and protists in SCS. Strong positive associations among autotrophic and heterotrophic groups were revealed in both niches. Therefore, the biotic interactions are also important and may be responsible for the unexplained variations of the abiotic factors from MRM models. Microbial network in the PRE estuarine water had weakened resistance to environmental disturbances, while the SCS network had greater capacity to maintain network stability. This study shed light on the different mechanisms of abiotic and biotic factors in shaping the compositions of bacteria and microeukaryotes between PRE and SCS niches, and highlights the weakening effect of environmental disturbances on the microbial network stability. Highlights: Salinity explained the largest variations to the microbial community in PRE. Spatial and environmental factors determined the microbes in SCS. Biotic interactions are responsible for the unexplained variations. PRE microbial network had weakened resistance to environmental disturbances. SCS microbial network had greater capacity to maintain network stability.